2016
DOI: 10.1089/brain.2016.0453
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Network Underpinning Novel Melody Creation

Abstract: Musical improvisation offers an excellent experimental paradigm for the study of real-time human creativity. It involves moment-to-moment decision-making, monitoring of one's performance, and utilizing external feedback to spontaneously create new melodies or variations on a melody. Recent neuroimaging studies have begun to study the brain activity during musical improvisation, aiming to unlock the mystery of human creativity. What brain resources come together and how these are utilized during musical improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Our research helps to better validate EEG findings into the investigation of brain activity underlying improvisation by utilizing advanced techniques (ASR, ICA and ICLabel) to clean and exclude artifacts from the data. Although body movement is an inherent part of playing a musical instrument, previous EEG research investigating improvisation has not used techniques such as ICA to separate brain activity from physiological and movement-based artifacts (Dolan et al, 2013(Dolan et al, , 2018Müller et al, 2013;Wan et al, 2014;Dikaya and Skirtach, 2015;Adhikari et al, 2016;Sanyal et al, 2016;Lopata et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research helps to better validate EEG findings into the investigation of brain activity underlying improvisation by utilizing advanced techniques (ASR, ICA and ICLabel) to clean and exclude artifacts from the data. Although body movement is an inherent part of playing a musical instrument, previous EEG research investigating improvisation has not used techniques such as ICA to separate brain activity from physiological and movement-based artifacts (Dolan et al, 2013(Dolan et al, , 2018Müller et al, 2013;Wan et al, 2014;Dikaya and Skirtach, 2015;Adhikari et al, 2016;Sanyal et al, 2016;Lopata et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous EEG research concerned with music improvisation has not used techniques such as ICA to separate brain activity from physiological and movementbased artifacts. Most EEG music improvisation studies use only simple band-pass filtering and amplitude-based trial rejection as well as subjective visual inspection techniques (Dolan et al, 2013(Dolan et al, , 2018Müller et al, 2013;Wan et al, 2014;Dikaya and Skirtach, 2015;Adhikari et al, 2016;Sanyal et al, 2016;Lopata et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We did not have predictions related to changes in connectivity as earlier studies utilizing the contrast between improvisation and memory retrieval did not report related changes in connectivity. We did, however, hypothesize that the superior temporal gyrus (STG) would be part of a network based on our prior electroencephalography study (Adhikari et al, 2016) and the location of the auditory cortices.…”
Section: Vocalizing and Imagining Improvisationsmentioning
confidence: 99%
“…Meanwhile, Müller et al ( 2013 ) found greater inter-brain synchronization of theta and delta oscillatory activity compared to higher frequency oscillatory activity during musical improvisation between two guitarists. Additionally, Adhikari et al ( 2016 ) attributed decreased coherence with frontal oscillatory brain activity during musical improvisation compared to during performance of pre-learned music as important to the spontaneity of improvisation. Network-based analysis has also been used to identify potential regions of interest during musical improvisation.…”
Section: Introductionmentioning
confidence: 99%